2023
DOI: 10.1186/s13046-023-02597-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-455-5p suppresses PDZK1IP1 to promote the motility of oral squamous cell carcinoma and accelerate clinical cancer invasion by regulating partial epithelial-to-mesenchymal transition

Abstract: Background Lymph node and distant metastasis contribute to poor outcomes in patients with oral squamous cell carcinoma (OSCC). The mechanisms regulating cancer migration and invasion play a key role in OSCC. Methods We determined migration and invasion ability of OSCC by wound-healing assay, two-chamber transwell invasion assay and cell mobility tracking and evaluated tumor metastasis in vivo. Western blot (WB), qRT-PCR, RNA-seq, dual-luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Here, we focused on miRNAs associated with the development and progression of human malignancies. Several miRNAs have been reported to function as oncogenes or tumor suppressor genes in OSCC [22][23][24][25][26]. In the present study, we showed that the downregulation of miR-375-3p expression was associated with latent cervical LNM of eOSCC, and the replenishment of miR-375-3p suppressed the growth and migration of human OSCC cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Here, we focused on miRNAs associated with the development and progression of human malignancies. Several miRNAs have been reported to function as oncogenes or tumor suppressor genes in OSCC [22][23][24][25][26]. In the present study, we showed that the downregulation of miR-375-3p expression was associated with latent cervical LNM of eOSCC, and the replenishment of miR-375-3p suppressed the growth and migration of human OSCC cells.…”
Section: Discussionsupporting
confidence: 59%
“…In particular, by regulating gene expression, miRNAs are greatly involved in biological processes such as cell proliferation, migration, infiltration, and apoptosis, which are essential for cancer development and progression [22]. In OSCC, several miRNAs have been reported to be associated with development and progression [22][23][24]. We have also reported several miRNAs that affect tumor growth in OSCC, including miR-361-3p and miR-1289 [25,26].…”
Section: Introductionmentioning
confidence: 78%
“…Two pathologists, blinded to the study, used a multiheaded microscope to assess protein expression. They evaluated the intensity and distribution to agree on the H-score, calculated as ΣPi (i + 1), where i indicates the intensity of stained cells (0: negative, 1: weak positive, 2: moderate positive, 3: strong positive), and Pi represents the percentage of stained cells (Hsiao et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many microRNAs (miRNAs and miRs) are associated with EMT in normal and cancer cells (6)(7)(8). However, only a few studies on the association between miRNAs and EMT have been published in veterinary medicine (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%